2022
DOI: 10.1210/jendso/bvac032
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Differentiated Thyroid Cancer Survival Is Unaffected by Mode of Preparation for 131I Administration

Abstract: Background and Objective Recombinant human thyrotropin (rhTSH) is currently not FDA-approved for the treatment of high-risk patients with differentiated thyroid cancer (DTC). The goal of our study was to compare the outcomes in higher risk patients with metastatic DTC prepared for radioiodine (RAI) therapy with rhTSH versus thyroid hormone withdrawal (THW). Methods Retrospective chart review of patients with metastatic DTC in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…However, due to the well-known drawbacks and potential health risks of THW, rhTSH has been explored as an alternative protocol for metastatic patients [ 107 ]. Some studies showed benefits and the same effectiveness of rhTSH preparation compared with THW [ 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ]. However, most of these cohorts are small and retrospective, and the follow-up of the patients treated with rhTSH is most often significantly shorter than that of the patients treated after THW, preventing any reliable conclusions ( Table 4 ).…”
Section: Radioiodine Treatment Goalsmentioning
confidence: 99%
“…However, due to the well-known drawbacks and potential health risks of THW, rhTSH has been explored as an alternative protocol for metastatic patients [ 107 ]. Some studies showed benefits and the same effectiveness of rhTSH preparation compared with THW [ 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ]. However, most of these cohorts are small and retrospective, and the follow-up of the patients treated with rhTSH is most often significantly shorter than that of the patients treated after THW, preventing any reliable conclusions ( Table 4 ).…”
Section: Radioiodine Treatment Goalsmentioning
confidence: 99%
“…We read with great interest the by paper by Christiane Gomes-Lima and colleagues, titled “Metastatic Differentiated Thyroid Cancer Survival Is Unaffected by Mode of Preparation for 131 I Administration” [ 1 ].…”
mentioning
confidence: 99%
“…The study describes 55 patients with metastatic differentiated thyroid carcinoma (DTC) who were treated with radioactive iodine (RAI) and compares the outcomes of patients prepared solely with recombinant human thyrotropin (rhTSH) or with thyroid hormone withdrawal (THW). The authors conclude that the mode of preparation for RAI therapy does not decisively affect the outcome of RAI therapy of patients with metastatic DTC [ 1 ].…”
mentioning
confidence: 99%
“…In our view, there is little doubt that use of recombinant human thyrotropin (rhTSH) has proved of significant benefit to patients with low- or intermediate-risk differentiated thyroid cancer (DTC). And in their communication regarding our study [ 1 ], Zandee and Links [ 2 ] present compelling arguments with which we fully agree on the importance and merits of also establishing that preparation by rhTSH for radioiodine (RAI) therapy of higher risk or metastatic DTC would be equally efficacious to preparation by thyroid hormone withdrawal. Insofar as our study did reach this conclusion, they express concern that we may have overstated that the results achieved by the 2 approaches were equivalent due to underpowering of the study.…”
mentioning
confidence: 71%